2013
DOI: 10.1186/1746-1596-8-173
|View full text |Cite
|
Sign up to set email alerts
|

Variable copy number of mitochondrial DNA (mtDNA) predicts worse prognosis in advanced gastric cancer patients

Abstract: BackgroundChange of mitochondrial DNA (mtDNA) copy number is widely reported in various human cancers, including gastric cancer, and is considered to be an important hallmark of cancers. However, there is remarkably little consensus on the value of variable mtDNA content in the prognostic evaluation of this cancer.MethodsUsing real-time quantitative PCR approach, we examined mtDNA copy number in a cohort of gastric cancers and normal gastric tissues, and explored the association of variable mtDNA content with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 38 publications
(46 reference statements)
3
57
0
1
Order By: Relevance
“…After a thorough review of titles and abstracts by two investigators independently, 394 studies were excluded and the full texts of remaining 26 references have also been artificial retrieved for further identification. Finally a total of 20 retrospective studies comprising 5413 patients were included in our study and 18 studies were used for analysis16171819202122252627282930313233343536. Among the included studies for analysis, there were 16 studies recruited Asian patients while 2 studies recruited Caucasian patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a thorough review of titles and abstracts by two investigators independently, 394 studies were excluded and the full texts of remaining 26 references have also been artificial retrieved for further identification. Finally a total of 20 retrospective studies comprising 5413 patients were included in our study and 18 studies were used for analysis16171819202122252627282930313233343536. Among the included studies for analysis, there were 16 studies recruited Asian patients while 2 studies recruited Caucasian patients.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies252735 reported mtDNA copy number as three categorical variables and all used middle level of mtDNA copy number as reference. All three studies recruited Asians and measured copy number in tissue.…”
Section: Resultsmentioning
confidence: 99%
“…38 An analysis of a different set of patients revealed that increased mtDNA copy number is associated with worse survival in patients with late-stage tumors. 41 In breast cancer, a decrease in mtDNA copy number was correlated with higher histological grade, poorer disease-free survival, and lower overall survival. 42 In colorectal cancer, patients with lower mtDNA copy number showed higher TNM stages and poorer differentiation.…”
Section: Copy Number Changesmentioning
confidence: 99%
“…Numerous tumors are characterized by an overexpression of uncoupling proteins, for instance, in human colorectal cancers [172174]. In particular, UCP2 appears to be overexpressed in leukemia and in other forms of cancer [146].…”
Section: Mitochondriamentioning
confidence: 99%